1999
DOI: 10.1074/jbc.274.34.24257
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interaction between Yeast Nucleotide Excision Repair Factors NEF2 and NEF4 in the Binding of Ultraviolet-damaged DNA

Abstract: Saccharomyces cerevisiae RAD4, RAD7, RAD16, and RAD23 genes function in the nucleotide excision repair (NER) of ultraviolet light (UV)-damaged DNA. Previous biochemical studies have shown that the Rad4 and Rad23 proteins are associated in a stoichiometric complex named NEF2, and the Rad7 and Rad16 proteins form another stoichiometric complex named NEF4. While NEF2 is indispensable for the incision of UV-damaged DNA in the in vitro reconstituted system, NEF4 stimulates the incision reaction. Both NEF2 and NEF4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 21 publications
(48 reference statements)
0
22
0
Order By: Relevance
“…Rad16 facilitates histone H3 acetylation after UV irradiation , however, and an effect of histone H3 methylation on NER at silenced loci has been reported (Chaudhuri et al 2009). Although not required for dual cleavage of UV-irradiated DNA in vitro, the Rad7-Rad16 complex markedly stimulates the reaction; combining Rad4-Rad23 and Rad7-Rad16 synergistically enhances binding to UV-damaged DNA (Guzder et al 1999). Finally, physical interaction between Rad4 and Rad7 allows the formation of a large lesion-recognition complex (Guzder et al 1999).…”
Section: ; Tremblay Et Al 2008)mentioning
confidence: 99%
See 1 more Smart Citation
“…Rad16 facilitates histone H3 acetylation after UV irradiation , however, and an effect of histone H3 methylation on NER at silenced loci has been reported (Chaudhuri et al 2009). Although not required for dual cleavage of UV-irradiated DNA in vitro, the Rad7-Rad16 complex markedly stimulates the reaction; combining Rad4-Rad23 and Rad7-Rad16 synergistically enhances binding to UV-damaged DNA (Guzder et al 1999). Finally, physical interaction between Rad4 and Rad7 allows the formation of a large lesion-recognition complex (Guzder et al 1999).…”
Section: ; Tremblay Et Al 2008)mentioning
confidence: 99%
“…Although not required for dual cleavage of UV-irradiated DNA in vitro, the Rad7-Rad16 complex markedly stimulates the reaction; combining Rad4-Rad23 and Rad7-Rad16 synergistically enhances binding to UV-damaged DNA (Guzder et al 1999). Finally, physical interaction between Rad4 and Rad7 allows the formation of a large lesion-recognition complex (Guzder et al 1999). These data clearly point to a role for Rad7-Rad16 in DNA damage recognition during GG-NER, and other studies suggest an additional role for Rad7-Rad16 in post-incision events ).…”
Section: ; Tremblay Et Al 2008)mentioning
confidence: 99%
“…No catalytic function has been associated with yeast Rad23 protein. The protein forms a tight complex with Rad4 protein (a protein with limited amino-acid sequence homology to human XPC protein) through its carboxy-terminal region (Guzder et al 1995;Wang et al 1997;Schauber et al 1998) and the Rad23/Rad4 complex has been shown to preferentially bind UV-irradiated DNA (Guzder et al 1998(Guzder et al , 1999Jansen et al 1998). The amino-terminal region of Rad23 protein contains a ubl domain that is required for optimal levels of NER in vivo.…”
mentioning
confidence: 99%
“…NER is a highly conserved process among eukaryotes from yeast to humans (36). In S. cerevisiae, NER is accomplished via the concerted action of the following: Rad14, RPA, the Rad4-Rad23 complex, and the Rad7-Rad16 complex, all of which function in DNA damage recognition (5,11,12,(14)(15)(16)22); TFIIH, which contains the Rad3 and Rad25 DNA helicases, essential for DNA unwinding (41); and the Rad1-Rad10 and Rad2 nucleases (18, 42, 43) which incise the damaged strand on the 5Ј and 3Ј sides of the lesion, respectively (2, 17). Both in yeast and humans, dual incision by the NER ensemble results in the release of an oligonucleotide fragment ϳ25 to 30 nucleotides long (10,28,29).…”
mentioning
confidence: 99%